(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
A victim is a product of crime and his rehabilitation and restoration in the society is an indispensable facet under criminal justice system. Victim compensation is one of the several modes of rehabilitation, reparation and assistance of the victim of a crime. But there is not a single comprehensive law which exclusively related to compensation and rehabilitation of victim of a crime. Under the Code of Criminal Procedure, 1973 there are many provisions relating to compensation of victim, but these are lengthy and not uniform throughout the country. A comprehensive law is much needed solution which exclusively deals with and provided for the victim a speedier mode of compensation, rehabilitation and assistance in criminal justice system.